The Impact of Preoperative Chronic Opioid Therapy in Patients Undergoing Decompression Laminectomy of the Lumbar Spine. Issue 7 (1st April 2020) - Kha, Stephanie T.; Scheman, Judith; Davin, Sara; Benzel, Edward C.
Abstract : Study Design: Retrospective review of electronic medical records (EMR). Objective: This study aims to (1) characterize the pattern of opioid utilization in patients undergoing spine surgery and (2) compare the postoperative course between patients with and without chronic preoperative opioid prescriptions. Summary of Background Data: Postoperative pain management for patients with a history of opioid usage remains a challenge for spine surgeons. Opioids are controversial in this setting due to side effects and potential for abuse and addiction. Given the increasing rate of opioid prescriptions for spine-related pain, more studies are needed to evaluate patterns and risks of preoperative opioid usage in surgical patients. Methods: EMR were reviewed for patients (age > 18) with lumbar spinal stenosis undergoing lumbar laminectomy in 2011 at our institution. Data regarding patient demographics, levels operated, pre/postoperative medications, and in-hospital length of stay were collected. Primary outcomes were length of stay and duration of postoperative opioid usage. Results: One hundred patients were reviewed. Fifty-five patients had a chronic opioid prescription documented at least 3 months before surgery. Forty-five patients were not on chronic opioid therapy preoperatively. The preoperative opioid group compared with the non-opioid group had a greater proportion of females (53% vs. 40%), younger mean age (63 yrs vs. 65 yrs), higher frequency of preoperative benzodiazepine prescription (20% vs. 11%), longer average in-hospital length of stay (3.7 d vs. 3.2 d), and longer duration on postoperative opioids (211 d vs. 79 d). Conclusion: Patients on chronic opioids prior to spine surgery are more likely to have a longer hospital stay and continue on opioids for a longer time after surgery, compared with patients not on chronic opioid therapy. Spine surgeons and pain specialists should seek to identify patients on chronic opioids before surgery and evaluate strategies to optimize pain management in the pre- and postoperative course. Level of Evidence: 3 Abstract : In this retrospective electronic medical records review of 100 patients undergoing lumbar laminectomy in 2011, 55% were on chronic opioid therapy preoperatively. The preoperative opioid group had a greater proportion of tobacco and benzodiazepine users, longer in-hospital length of stay, and longer duration on postoperative opioids compared with the non-opioid group.